Dividend policy, profitability, institutional ownership, firm size, corporate social responsibility on firm value - Rahmawati, Alni; Sistafiani, Dian (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
The purpose of this research is to examine and analyze the influence of dividend policy, profitability, institutional ownership, firm size, and Corporate Social Responsibility to firm value. The object of this research is a manufacturing company listed on the Indonesia Stock Exchange (IDX) period 2015-2019. The data used in this study is secondary data in the form of annual financial statements. The sample was chosen by using purposive sampling method and obtained by 63 companies. The analytical method used in this study used multiple linear regression with E-Views 7.1 application tool. The result of the research shows that dividend policy has a significant positive effect on firm value, profitability has positive significant influence to the firm value, institutional ownership has positive significant influence to the firm value, firm size has significant positive influence to the firm value, and Corporate Social Responsibility (CSR) has significant negative influence to the firm value.